Avaliação da influência do resíduo de vidro utilizado como agregado miúdo nas propriedades do concreto. - Rollim, Isabelle Vasconcelos (2019)
One of the alternatives to mitigate the impacts caused by the extraction of mineral resources, and which has been studied by the civil construction sector, is the use of waste from recycling processes in the production of cementitious composites. Recent studies have shown that glass waste can be used in the manufacture of cementitious composites, either as fine and coarse aggregate or as a partial substitute for cement. The use of recycled glass aggregates provides the advantage of reducing the consumption of natural aggregates and encourages the proper disposal of these wastes. The main objective of this research is to evaluate the influence of the use of glass waste as a partial substitute for the natural fine aggregate (sand) on the physical, mechanical and durability properties of concrete. The methodology consisted of performing laboratory tests on cylindrical concrete specimens and mortar bars in the percentages of substitution of 0%, 15% and 30% of the sand by the glass waste, at ages of 7, 28 and 148 days. The properties were analyzed through tests of consistency, specific mass, compressive strength, tensile strength by diametrical compression, dynamic modulus of elasticity, water absorption and expansibility of the mortar bars. As a result, there was a 30% reduction in workability for concretes and a reduction in mechanical strength, and the results of specific mass and water absorption had no significant differences. At 28 days of age, the reference concrete obtained compressive strength of 24.98 MPa, and the samples with 15% and 30% of replacement showed reductions of 5% and 15%.Considering the expansion of AAR, the concrete with glass residue was classified as potentially reactive, and specific care should be taken to mitigate a possible expansion of AAR. It was concluded that the results point to the technical feasibility of using glass waste as a fine aggregate in the production of nonstructural concrete, thus presenting an alternative for reducing the extraction of natural resources and also an environmental solution for the disposal and reuse of glass waste in the civil construction sector.